Dual Home and Dual Exile of Jan Cep? - Novotny, Vladimir (Bohemica Olomucensia, 2015)
One of the basic categories which are applied on the interpretation of Jan Cep's work is the author's own credo called ``dioecy'', i.e., the concept of dual home, mostly differentiated as a notion of an inner and outer home. These notions acquire additional meanings particularly with a consideration of Cep's life experience, of his exile, and especially of his reflections about a true homeland or a ``second homeland'', however, these notions are essential in terms of reflecting his indigenous pilgrimage. Cep has developed this life-time and creative philosophy in his literary journalism and essays, most significantly in his late essayistic exile memoirs Sestra uzkost.
Keywords: Prose works by Jan Cep; dioecy; dual home; second homeland; exile